A Novel Approach to Development of Renewable Heating Support Policies in Turkey - Ates, Seyithan Ahmet (International Journal of Energy Economics and Policy, 2013)
In Turkey, potential of renewable energy for both heating and cooling systems remains mostly untapped. Turkey’s energy demand is met to a great extent by imported energy sources which constitutes a substantial economic burden for Turkey. The main types of supporting financial mechanisms are limited to feed-in tariff for electricity production. The first aim of this paper is, to analyze current best practice policy design and harmonization of support schemes for renewable heating technologies in European countries. Secondly, the paper proposes a two steps model to develop support mechanisms for renewable heating technologies in Turkey. The paper analyzed the impacts of different policy harmonization options in the field of renewable energy heating and cooling, taking into account various determinants such as survey of current best-available RE policies in Europe, available national RE potential, data on different regional characteristics of Turkey, accompanying regulations, laws and implementation measures, support policies with regard to domestic RE technologies. Based on the bottom-up modeling, the scheme shows that a harmonized use of different inputs would generate a comprehensive policy instruments, such as subsides, regulations and local targets. Keywords: Renewable energy, Energy economics, Renewable heating technologies, Policy design, Global warming JEL Classifications: Q20; Q28; Q48; Q58